Analysis Of Social Responsibility Of PT Angkasa Pura Indonesia In The Implementation Of Sustainable Development Goals - Rizki, Amelia Wardatus; Bhayangkara, Ida Bagus Ketut (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research seeks to analyze the application of Sustainable Development Goals values in the CSR Social Responsibility program in the Indonesian aviation industry implemented by PT Angkasa Pura Indonesia and how it is relevant to the CSR standards used by the company as a standard for preparing sustainability reports. This research takes PT Angkasa Pura Indonesia as the object considering that the company is a state-owned company that manages major airports in various regions in Indonesia. This research uses a qualitative content analysis method. This study found that the CSR programs carried out by the company have SDGs value applications that vary depending on the field and type of program. The applied values are also disclosed by the company through its sustainability report.